Recent advances in understanding oxidative stress in sepsis: pathogenic roles and antioxidant therapeutic prospects - a narrative review - Lin, Yijuan; Alhaskawi, Ahmad; Chen, Lin; Moqbel, Safwat Adel Abdo (Frontiers in Pharmacology, 2025)
Sepsis remains a major global health challenge, exerting a particularly severe toll in low- and middle-income countries. Despite advances in antimicrobial and supportive care, sepsis continues to defy effective control due to its complex pathophysiology and multi-organ involvement. Central to this complexity is a dysregulated host response, driven by hyperinflammation, immune suppression, and profound mitochondrial and metabolic dysfunction. A critical mediator of this dysregulation is oxidative stress, which exacerbates cellular injury through reactive oxygen and nitrogen species, disrupting mitochondrial integrity and redox balance. This review synthesizes current insights into the mechanistic interplay between oxidative stress, mitochondrial dysfunction, and immunopathology in sepsis. It further evaluates the therapeutic potential of endogenous antioxidants, such as superoxide dismutase, catalase, and glutathione, as well as exogenous agents including vitamins A, C, E, selenium, omega-3 fatty acids, melatonin, and carnosine. While translational gaps persist, particularly in dosing, timing, and patient stratification, emerging strategies including mitochondria-targeted antioxidants, nanotherapeutics, and biomarker-guided interventions hold promise for restoring redox homeostasis and improving clinical outcomes. This review aims to serve as a contemporary resource for researchers and clinicians striving to decode the oxidative basis of sepsis and accelerate the development of precision antioxidant therapies.